Efforts to increase the understanding of productive waqf for 'Aisyiyah Board in South Tangerang City - Oneng Nurul Bariyah; Ali Idrus; Mutiara Shafwah (Universitas Muhammadiyah Magelang, 2022)
Following the foundation of the South Tangerang City government, the 'Aisyiyah board was established. This has an impact on the position of business charities in the South Tangerang City area, which was once part of Tangerang Regency and Tangerang City. There are waqf assets that are corporate charities with the status of two foundation entities, and the name Nadzir is still an individual. As a result, the program aims to improve the 'Aisyiyah board's understanding of waqf, systematize the administration of waqf assets, and maintain waqf objects in accordance with waqf's purposes and advantages. Data collecting, socialization, analysis of the waqf deed, and amending of the deed are the methods used. The following are the outcomes of the activity: first, the accomplishment of an agreement by the 'Aisyiyah board in South Tangerang City to modify the administration of recording nazdir in the Waqf Pledge Deed, which is not in compliance with regulations. Second, it is documented that the waqf Pledge Deed data will be amended for individual nadzir data in order for Persyarikatan Muhammadiyah to become a legal organization nadzir. Third, the 'Aisyiyah board in South Tangerang City has reached an agreement to maintain and develop waqf assets in the form of educational institutions, and others.